2014
DOI: 10.1371/journal.pone.0114909
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Mechanism of BNG-1 against Focal Cerebral Ischemia: A Neuroimaging and Neurotrophin Study

Abstract: BNG-1 is a herb complex used in traditional Chinese medicine to treat stroke. In this study, we attempted to identify the neuroprotective mechanism of BNG-1 by using neuroimaging and neurotrophin analyses of a stroke animal model. Rats were treated with either saline or BNG-1 for 7 d after 60-min middle cerebral artery occlusion by filament model. The temporal change of magnetic resonance (MR) imaging of brain was studied using a 7 Tesla MR imaging (MRI) system and the temporal expressions of neurotrophin-3 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The BNG-1 has neuroprotective effect against ischemic injury which can be seen in animals receiving BNG-1 before as well as after middle cerebral artery (MCA) occlusion and has anti-thrombotic activity to inhibit arachidonic acid-induced platelet aggregation in vitro and prolong bleeding time in mice in vivo 20 . Our previous study using 7T MR neuroimaging and neurotrophin analyses in rat MCA occlusion model 22 found the neuroprotective effect of BNG-1 may act through recovery of cerebral hemodynamics, decrease of infarction size and edema, reduction of postischemic hyperperfusion injury and recovery of neurotrophn-3 and brain-derived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 98%
“…The BNG-1 has neuroprotective effect against ischemic injury which can be seen in animals receiving BNG-1 before as well as after middle cerebral artery (MCA) occlusion and has anti-thrombotic activity to inhibit arachidonic acid-induced platelet aggregation in vitro and prolong bleeding time in mice in vivo 20 . Our previous study using 7T MR neuroimaging and neurotrophin analyses in rat MCA occlusion model 22 found the neuroprotective effect of BNG-1 may act through recovery of cerebral hemodynamics, decrease of infarction size and edema, reduction of postischemic hyperperfusion injury and recovery of neurotrophn-3 and brain-derived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 98%
“…The cAMP-dependent lipolysis in adipose tissues was shown to be activated by ROS and TNF-α 21 , 22 . Additionally, BNG-1 has previously been shown to be a non-specific inhibitor of artery cAMP-dependent PDEs including PDE-1 to -6 8 . The present results showed that the BNG-1 can exert a dual effect on the cAMP activities and PDE3B expression of target tissues and affect the oxidative stress status.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese medicinal formula BNG-1 is composed of a number of herbs, which are thought to be effective for the treatment of stroke. BNG-1 has been shown to exert its anti-inflammatory activity by suppression of different phosphodiesterases (PDEs) 8 . PDEs are known to hydrolyze both cAMP and cGMP to the inactive forms and are involved in cellular signaling transduction.…”
Section: Introductionmentioning
confidence: 99%
“…As described in detail previously [ 20 ], inhalation of a nitrous oxide/oxygen/isoflurane mixture (70%/30%/1.5%) was used to anesthetize the rats before MRI. After exposing the inguinal area, a biomedical silicone catheter (external diameter of 0.64 mm) was cannulated into left femoral vein to administer MR contrast agent.…”
Section: Methodsmentioning
confidence: 99%